2019
DOI: 10.1109/access.2019.2954858
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Vehicle Sensing via Asynchronous V2V Transmission: A Multi-Path-Geometry Approach

Abstract: Accurate vehicular sensing is a basic and important operation in autonomous driving. Unfortunately, the existing techniques have their own limitations. For instance, the communication-based approach (e.g., transmission of GPS information) has high latency and low reliability while the reflection-based approach (e.g., RADAR) is incapable of detecting hidden vehicles (HVs) without line-of-sight. This is arguably the reason behind some recent fatal accidents involving autonomous vehicles. To address this issue, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Most studies in the field of material identification have only focused on single-bounce-reflection [3] [4], that is, it is assumed that single-bounce-reflection trajectories are always available (single-bounce-assumption) [5]. For example, in [3], the authors demonstrated how permittivity obtained from reflected radio signals can be used to identify the material of reflecting surface.…”
Section: Related Workmentioning
confidence: 99%
“…Most studies in the field of material identification have only focused on single-bounce-reflection [3] [4], that is, it is assumed that single-bounce-reflection trajectories are always available (single-bounce-assumption) [5]. For example, in [3], the authors demonstrated how permittivity obtained from reflected radio signals can be used to identify the material of reflecting surface.…”
Section: Related Workmentioning
confidence: 99%
“…4. This paper assumes single-bouncereflection path between TX and RX and does not consider multiple-bounce paths that have larger time of arrival (TOA) and weaker received signal strength (RSS) for the evaluation purpose [12]. Wall made up of materials listed in Table I is considered to generate a single-bounce path between TX and RX.…”
Section: Numerical Validationmentioning
confidence: 99%
“…3) Compatibility with Existing Algorithms: CDA can work well with various positioning algorithms according to available measurements, extending its usage into various applications. For example, when the multi-path profile of a wireless propagation is given in terms of AoA, AoD, and delay as in [6], it is possible to find multiple PELs by selecting a few paths among the entire ones. Besides, CDA helps pedestrian dead reckoning (PDR) [7], a positioning algorithm using IMU's sequential measurements.…”
Section: B Advantage Of Combinatorial Data Augmentationmentioning
confidence: 99%